2022
DOI: 10.1108/jhti-01-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

The local food supply, willingness to pay and the sustainability of an island destination

Abstract: PurposeThe purpose of this study is to examine the trend toward purchasing locally grown food and evaluate if tourists visiting Hawai'i are willing to pay more for locally produced foods that are more ecologically sustainable.Design/methodology/approachA research questionnaire was developed in order to investigate the attitudes and behaviors of tourists from the continental United States visiting Hawai'i in purchasing locally grown food in Hawai'i. The final sample includes 454 valid survey responses collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…In addition, LFQP may influence other aspects of the dining experience. For example, a study by Linnes et al (2022) [25] revealed that consumers who eat at local restaurants feel more connected to their community, and this leads consumers to have higher levels of DS.…”
Section: The Effect Of Lfqp On Dsmentioning
confidence: 99%
“…In addition, LFQP may influence other aspects of the dining experience. For example, a study by Linnes et al (2022) [25] revealed that consumers who eat at local restaurants feel more connected to their community, and this leads consumers to have higher levels of DS.…”
Section: The Effect Of Lfqp On Dsmentioning
confidence: 99%
“…The use of locally sourced ingredients in restaurants could also be perceived as valuable to some consumers. Research has shown that many consumers were willing to pay a premium for locally grown or produced food (Frash et al, 2015;Lang et al, 2014;Linnes et al, 2023;Remar et al, 2016). A study showed that the willingness to pay more for organic, local and fair-trade produce was mostly driven by beliefs in positive impacts on the local economy, the natural environment, social fairness and the society (Rainbolt et al, 2012), suggesting that consuming organic or local food may be associated with altruistic value to some consumers.…”
Section: Segmenting Restaurant Consumersmentioning
confidence: 99%
“…Oahu, the most visited island in the state of Hawaii, generates $7.7 billion of the overall tourism dollars, with Maui generating the second highest amount of tourism dollars with $3.5 billion (Hawaii Tourism Authority 2020). For years, Hawaii has depended on the tourism industry as the leading employer as well as the economic engine and its main source of income for Hawaii's economy (Agrusa 1994;Linnes et al 2014). The tourism industry accounted for over 150,000 employment opportunities for the state of Hawaii in 2017 (Department of Business and Economic Development and Tourism 2018).…”
Section: Introductionmentioning
confidence: 99%